HORMONE DISORDERS AND ITS CORRELATION WITH LIPID PROFILE AND OXIDATIVE STRESS BIOMARKERS IN METABOLIC SYNDROME PATIENTS - KHALEEL , SHUKRIYA M.; MOSA, AZZAM A. (Journal of Duhok University, 2023)
Background and aims: Metabolic syndrome" (MS) refers to a group of interrelated metabolic risk factors of developing cardiovascular disease (CVD) and type 2 diabetes mellitus (T2DM). The aim of this work is investigation the correlation of melatonin and sprosin hormones with lipid profile and oxidant/antioxidant status in sera of MS patients and to assess the potential of these parameters as diagnostic biomarkers for metabolic syndrome using receiver-operating characteristic (ROC) curve analysis Methods: This case-control study involved 82 MS patients and 60 controls. The study examined serum levels of glucose, melatonin, asprosin, lipid profile, malondialdehyde (MDA), superoxide dismutase (SOD), glutathione-S-transferase (GST), reduced glutathione (GSH), and total antioxidant activity (AOA). Results: The patients group had significantly lower serum levels of melatonin hormone, SOD, GST, GSH, and AOA. While, glucose and asprosin levels increased in MS patients compared to the controls. Similarly, the lipid profile, including cholesterol, very low density lipoprotein (VLDL), and triglyceride (TG), and low density lipoprotein (LDL), were significantly increased. Furthermore, correlation analysis revealed that levels of melatonin were negatively associated with cholesterol and positively associated with TG. Asprosin has negative significant correlation with GSH. Regarding ROC curve analysis, glucose, asprosine, VLDL, TG, and MDA were demonstrated as diagnostic biomarkers for metabolic syndrome. Conclusions: The study found that melatonin hormone was negatively associated with cholesterol and positively associated with TG, while Asprosin has negative significant correlation with GSH. Additionally, this study proved also that glucose, asprosin, VLDL, TG, and MDA can be used as metabolic syndrome’s predictive biomarkers